100 Years of Vitamin E: From Discovery to Commercialization. Issue 45 (1st December 2022) - Müller, Marc‐André; Schäfer, Christian; Litta, Gilberto; Klünter, Anna‐Maria; Traber, Maret G.; Wyss, Adrian; Ralla, Theo; Eggersdorfer, Manfred; Bonrath, Werner
Abstract: 2022 marks the centenary of the discovery of vitamin E by Evans and Bishop, an important milestone in vitamin research. An enormous amount of scientific data related to the importance of its activity has been published on this micronutrient. Globally, researchers from industry and academia have contributed to improve and implement highly efficient and commercially viable production processes for vitamin E. All processes share a common final step, but differ in the generation of their key building blocks. Today, Vitamin E, accounts for a worldwide production of >75.000 t/a. Vitamin E is applied predominantly as feed supplement for various animal species and in addition is used in a variety of human applications. Moreover, its impressive antioxidative behavior enables frequent use as stabilizing ingredient in many product forms and final consumer applications. This review will provide the current state of science, with clear focus on highlighting the different routes for industrial syntheses of vitamin E. Furthermore, approaches directed towards successful product form development including suitable auxiliary substances combined with appropriate formulation technologies, as well as a broad variety of applications in animal and human nutrition and health will be discussed. Insights on isolation approaches, biosynthesis, and future trends complete the status of Vitamin E research. Abstract : This review article provides the current state of science in the field of vitamin E, focusing on the industrial production. Additionally, formulation approaches as well as the many applications in animal and human nutrition and health, biosynthesis, isolation approaches and future trends are discussed.